Head nodding: An unusual presentation of congenital brain tumor - Bhalla, Kapil; Mehra, Shuchi; Gupta, Ashish; Nanda, Sanjiv (Indian Journal of Child Health, 2019)
Congenital brain tumors (CBTs) in neonates are defined as tumors presenting within 60 days after birth. Teratoma is the most common type of CBT. A 37-day-old baby was presented to pediatric emergency with complaints of difficulty in breathing, refusal of feed, and lethargy. The baby had continuous head nodding, drooling of saliva, and slight hypotonia of lower limbs which mother, then confirmed, was present since birth. There was a history of admission to another hospital with similar complaints at day 15 of life, where the child was discharged after 5 days of hospitalization with a diagnosis of nasal block. Magnetic resonance imaging brain showed a large mass located centrally suggestive of either pilocytic astrocytoma or medulloblastoma. The patient expired after 6 months in a private hospital. The present case report aims to focuse the importance of an early diagnosis based on the clinical presentation and imaging studies followed by timely intervention which is critical as the prognosis is very poor.